2014
DOI: 10.1371/journal.pone.0089911
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Patterns and Stimulus Control in Intermittent and Daily Smokers

Abstract: Intermittent smokers (ITS) – who smoke less than daily – comprise an increasing proportion of adult smokers. Their smoking patterns challenge theoretical models of smoking motivation, which emphasize regular and frequent smoking to maintain nicotine levels and avoid withdrawal, but yet have gone largely unexamined. We characterized smoking patterns among 212 ITS (smoking 4–27 days per month) compared to 194 daily smokers (DS; smoking 5–30 cigarettes daily) who monitored situational antecedents of smoking using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
149
2
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 120 publications
(166 citation statements)
references
References 70 publications
10
149
2
2
Order By: Relevance
“…18,37 Briefly, participants were asked to record each time they smoked a cigarette (event-based sampling); on a randomlyselected subset of occasions (4-5 per day), participants were asked a series of questions about the situation they were in. Further, to compare participants' situations when they were not smoking (signalbased sampling), participants were also "beeped" 4-5 times a day at random and asked to complete parallel assessments of nonsmoking situations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…18,37 Briefly, participants were asked to record each time they smoked a cigarette (event-based sampling); on a randomlyselected subset of occasions (4-5 per day), participants were asked a series of questions about the situation they were in. Further, to compare participants' situations when they were not smoking (signalbased sampling), participants were also "beeped" 4-5 times a day at random and asked to complete parallel assessments of nonsmoking situations.…”
Section: Methodsmentioning
confidence: 99%
“…These mood data were characterized using factor analysis into the sub-scales: negative affect, positive affect, arousal and inattention. 18 Factor scores thus derived are standardized T-scores (M = 50, SD = 10).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of this idea, research by Shiffman and colleagues showed that there were differences in the extent to which situational cues predicted smoking in occasional smokers compared to daily smokers, such that occasional smoking was more strongly associated with environmental cues (e.g. being away from home, in a bar, being with friends; Shiffman et al 2014). Thus, identifying how the content of consumers' situated conceptualizations differs according to key demographic factors is an important first step in the design of interventions that remove or reduce exposure to salient cues in the consumer environment.…”
Section: Removing or Reducing Exposure To Situational Cues That Activmentioning
confidence: 99%